EARLY FLOWERING3 Regulates Flowering in Spring Barley by Mediating Gibberellin Production and FLOWERING LOCUS T Expression . Issue 4 (29th April 2014) - Boden, Scott A.; Weiss, David; Ross, John J.; Davies, Noel W.; Trevaskis, Ben; Chandler, Peter M.; Swain, Steve M.
Abstract : This work shows that the early flowering and growth phenotypes of mutants of barley EARLY FLOWERING3 are promoted by increased production of gibberellin (GA). The authors find that GA is required for flowering and inflorescence development in spring barley grown under long-day conditions and that the GA-dependent control of flowering in barley is independent of FLOWERING LOCUS T1 activity. Abstract: EARLY FLOWERING3 ( ELF3 ) is a circadian clock gene that contributes to photoperiod-dependent flowering in plants, with loss-of-function mutants in barley ( Hordeum vulgare ), legumes, and Arabidopsis thaliana flowering early under noninductive short-day (SD ) photoperiods. The barley elf3 mutant displays increased expression of FLOWERING LOCUS T1 ( FT1 ); however, it remains unclear whether this is the only factor responsible for the early flowering phenotype. We show that the early flowering and vegetative growth phenotypes of the barley elf3 mutant are strongly dependent on gibberellin (GA ) biosynthesis. Expression of the central GA biosynthesis gene, GA20oxidase2, and production of the bioactive GA, GA1, were significantly increased in elf3 leaves under SDs, relative to the wild type. Inhibition of GA biosynthesis suppressed the early flowering of elf3 under SDs independently of FT1 and was associated with altered expression of floral identity genes at the developing apex. GA is also required for normal flowering of spring barley under inductive photoperiods, with chemical and genetic attenuation of the GA biosynthesis and signaling pathways suppressing inflorescence development under long-day conditions. These findings illustrate that GA is an important floral promoting signal in barley and that ELF3 suppresses flowering under noninductive photoperiods by blocking GA production and FT1 expression.